Study on solitary wasps of the subfamily Eumeninae (Hymenoptera: Vespidae) in Huu Lien and Na Hang nature reserves, with new records of one genus and three species - Lien, Nguyen Thi Phuong; Ha, Nguyen Thi Thu; Tuan, Luong Viet; Ngan, Doan Hong; Nga, Cao Thi Thanh (Academia Journal of Biology, 2018)
The composition of solitary wasps belonging to subfamily Eumeninae (Vespidae: Hymenoptera) in Huu Lien and Na Hang Nature Reserves has been surveyed. These are two study sites representing two sub-ecological zones, Cao Bang–Lang Son and Tuyen Quang–Ha Giang, which are at altitude below 300 m. As the results, a total of 29 species in 20 genera was recorded in both study sites, of them, 23 species in 16 genera were recorded in Huu Lien, and 23 species in 18 genera were recorded in Na Hang. Among them, one species Allorhynchium lugubrinum (Cameron, 1990) has been recorded only in Tuyen Quang–Ha Giang sub-ecological zone. Among the recorded taxa, the genus Antodynerus was newly recorded in Vietnam, and represented by one species Antodynerus limbatus (de Saussure, 1852). Another two species, Allorhynchium lugubrinum (Cameron, 1990) and Stenodyneriellua guttulatus (de Saussure, 1852) were recorded inVietnam for the first time.